Electrical recordings from dendritic spines of adult mouse hippocampus and effect of the actin cytoskeleton - Priel, Avner; Dai, Xiao-Qing; Chen, Xing-Zhen; Scarinci, Noelia; Cantero, María del Rocío; Cantiello, Horacio F. (Frontiers in Molecular Neuroscience, 2022)
Dendritic spines (DS) are tiny protrusions implicated in excitatory postsynaptic responses in the CNS. To achieve their function, DS concentrate a high density of ion channels and dynamic actin networks in a tiny specialized compartment. However, to date there is no direct information on DS ionic conductances. Here, we used several experimental techniques to obtain direct electrical information from DS of the adult mouse hippocampus. First, we optimized a method to isolate DS from the dissected hippocampus. Second, we used the lipid bilayer membrane (BLM) reconstitution and patch clamping techniques and obtained heretofore unavailable electrical phenotypes on ion channels present in the DS membrane. Third, we also patch clamped DS directly in cultured adult mouse hippocampal neurons, to validate the electrical information observed with the isolated preparation. Electron microscopy and immunochemistry of PDS-95 and NMDA receptors and intrinsic actin networks confirmed the enrichment of the isolated DS preparation, showing open and closed DS, and multi-headed DS. The preparation was used to identify single channel activities and “whole-DS” electrical conductance. We identified NMDA and Ca2+-dependent intrinsic electrical activity in isolated DS and in situ DS of cultured adult mouse hippocampal neurons. In situ recordings in the presence of local NMDA, showed that individual DS intrinsic electrical activity often back-propagated to the dendrite from which it sprouted. The DS electrical oscillations were modulated by changes in actin cytoskeleton dynamics by addition of the F-actin disrupter agent, cytochalasin D, and exogenous actin-binding proteins. The data indicate that DS are elaborate excitable electrical devices, whose activity is a functional interplay between ion channels and the underlying actin networks. The data argue in favor of the active contribution of individual DS to the electrical activity of neurons at the level of both the membrane conductance and cytoskeletal signaling.